2021
DOI: 10.1371/journal.pcbi.1009479
|View full text |Cite
|
Sign up to set email alerts
|

Cortical feedback and gating in odor discrimination and generalization

Abstract: A central question in neuroscience is how context changes perception. In the olfactory system, for example, experiments show that task demands can drive divergence and convergence of cortical odor responses, likely underpinning olfactory discrimination and generalization. Here, we propose a simple statistical mechanism for this effect based on unstructured feedback from the central brain to the olfactory bulb, which represents the context associated with an odor, and sufficiently selective cortical gating of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…This implies that theories of feedback and neurogenesis in the bulb that rely on specific targeting of GCs and MCs [ 12 , 28 , 98 ] may require additional components beyond the basic MC-GC network to be feasible. Interestingly, however, when we used this model in a recent study to examine the effect of GC feedback on cortical odor representation, we found that even highly correlated feedback patterns to GCs in a given network configuration produced robust odor discrimination following cortical transformation of the OB output [ 53 ]. This suggests that differential inhibition of MC firing may not be necessary to produce meaningful separation of odor patterns in cortex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that theories of feedback and neurogenesis in the bulb that rely on specific targeting of GCs and MCs [ 12 , 28 , 98 ] may require additional components beyond the basic MC-GC network to be feasible. Interestingly, however, when we used this model in a recent study to examine the effect of GC feedback on cortical odor representation, we found that even highly correlated feedback patterns to GCs in a given network configuration produced robust odor discrimination following cortical transformation of the OB output [ 53 ]. This suggests that differential inhibition of MC firing may not be necessary to produce meaningful separation of odor patterns in cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Our model reproduced important empirical features of the OB, including differential connectivity patterns among sister and non-sister MCs, decorrelation over short timescales, as well as theta, beta and gamma oscillations in the local field potential (LFP). The model makes the surprising, and testable, prediction that cortical feedback inhibition of MCs via GCs is a network property largely independent of which GCs are targeted, an observation with consequences for our understanding of how context modulates odor representations [ 28 , 44 53 ], and for theories of the functional purpose of granule cell neurogenesis [ 12 , 21 , 26 , 36 ]. The model also predicts that beta and gamma oscillations, which are implicated in numerous theories of odor coding and decoding [ 54 57 ], are network properties intrinsic to the bulb that can be modified, suppressed, or enhanced by the extent of granule cell activity [ 14 , 23 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes may be entrained by the extensive feedback that is present from the central brain to the olfactory bulb. Interestingly, recent work (Tavoni et al, 2021 ; Kersen et al, 2022 ) suggests that these feedback effects of context and valence need not be structured, and instead can also be disordered. That is, each behavioral context can effectively be represented as a random vector of feedback to the circuit elements of the bulb.…”
Section: Discussionmentioning
confidence: 99%